(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Pakshaghata is one of the Vatavyadhi considered under Ashtaumahagada according to different Aacharya’s. Pakshaghata can be correlated with hemiplegia, a condition caused by cerebrovascular accidents. The present study is a case report on management of hemiplegia of a female patient aged 65 years with chief complaints of weakness in right upper and lower limb. The case treated with the Ayurvedic medications, Panchkarma procedures and physiotherapy. Treatment protocol was Snehana, Swedana, Nasya, Kalabasti, Mridu virechana along with Shamana aushadhi. After the above treatment there was remarkable improvement in function of right lower and upper extremity, at the end of the treatment she could walk without support.